MINAT SISWA KELAS IV DI UPTD SDN 1 TANJUNGSARI MENGENAI PENGAJARAN GERAK DASAR ATLETIK - Zaenal Arifin; Mochamad Zakky Mubarok; Fauzan Effendy (STKIP Subang, 2026)
Physical Education is the right medium to develop children's motor skills. One of the materials in physical education at the elementary school level is basic athletic movements. The application of the material has not been maximized because students' interest in doing the teaching is still low. Some of the factors that cause low interest are that students prefer other sports, students are not serious during learning, and the way teachers teach seems to have no innovation. Therefore, this study aims to determine the interest of class IV students at UPTD SD Negeri 1 Tanjung Sari. The method applied in this research is descriptive method and completed by collecting questionnaires given to grade IV students at the school. The results showed that the interest of grade IV students at the school in basic athletic movement material was in the “very low” category of 0%, the “low” category of 36%, the “moderate” category of 32%, the ‘high’ category of 16%, and the “very high” category of 16%. This finding indicates the need for more innovative and interesting teaching strategies to increase students' interest in participating in teaching basic athletic movements.